PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Ningsih, Manggar Wigati; Laksito, Herry (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the audit committee characteristics that influencing the intellectual capital disclosure at the financial companies listed on the Stock Exchange in 2010 until 2012. The audit committee characteristics that was used in this research are audit committee size, number of audit committee meetings, and Â financial expertise on the audit committee which are independent variables. Board independence, listing age, profitability, and firm size are control variables. The intellectual capital disclosure is the dependent variable. The population of this research are all financial companies listed on the Stock Exchange in 2010 until 2012. Total research sample is 63 financial firms that selected with purposive sampling. This research analyzes the company's annual report using the method of content analysis. Data analyzed with test of classical assumptions, test of hypothesis, and multiple linear regression analysis method. The results of this research indicate that audit committee size and number of audit committee meetings have positively significant effect to the overall intellectual capital disclosure. Independence of audit committee and financial expertise have no significant effect to the intellectual capital disclosure.